PENGARUH KOMUNIKASI TERHADAP PENYELESAIAN TUGAS DI SUB BAGIAN PENGKAJIAN SEKRETARIAT DPRD KABUPATEN KUTAI TIMUR - Taslim, Taslim (PREDIKSI, 2016)
This study is intended to determine the effect of communication on the completion of tasks in Subdivision Assessment East Kutai Regency Secretariat therefore the researchers to formulate hypotheses